Antinociceptive Effect Of The Essential Oil Of Zingiber Zerumbet In Mice: Possible Mechanisms - Mohamed Hanief Khalid ,; Muhammad Nadeem Akhtar,; Azam Shah Mohamad,; Enoch Kumar Perimal,; Ahmad Akira,; Daud Ahmad Israf,; Nordin Lajis,; Mohd Roslan Sulaiman (Elsevier, 2024)
Ethnopharmacological relevance: Zingiber zerumbet (L.) Smith, a wild edible ginger species or locally known as "lempoyang", commonly used in the Malays traditional medicine as an appetizer or to treat stomachache, toothache, muscle sprain and as a cure for swelling sores and cuts.